α-melanocyte stimulating hormone modulates the central acyl ghrelin-induced stimulation of feeding, gastrointestinal motility, and colonic secretion - Huang HH; Chen LY; Doong ML; Chang SC; Chen CY (Dove Medical Press, 2017)
Hsien-Hao Huang,1,2 Liang-Yu Chen,3,4 Ming-Luen Doong,5 Shi-Chuan Chang,6,7 Chih-Yen Chen8–10 1Institute of Clinical Medicine, National Yang-Ming University of Medicine, 2Department of Emergency Medicine, Taipei Veterans General Hospital, 3Aging and Health Research Center, National Yang-Ming University, 4Center for Geriatrics and Gerontology, Taipei Veterans General Hospital, 5Institute of Physiology, National Yang-Ming University School of Medicine, 6Institute of Emergency and Critical Medicine, National Yang-Ming University School of Medicine, 7Department of Chest Medicine, Taipei Veterans General Hospital, 8Division of Gastroenterology and Hepatology, Department of Medicine, Taipei Veterans General Hospital, 9Faculty of Medicine, National Yang-Ming University School of Medicine, Taipei, 10Taiwan Association for the Study of Small Intestinal Diseases, Guishan, Taiwan Background: Acyl ghrelin-induced intake depends on hypothalamic neuropeptide Y and agouti-related protein (AgRP) neurotransmitters. Intracerebroventricular (ICV) injection of AgRP increases feeding through competitive antagonism at melanocortin receptors. ICV administration of α-melanocyte stimulating hormone (α-MSH), a natural antagonist of AgRP, may modulate the acyl ghrelin-induced orexigenic effect.Objective: This study aimed to investigate the modulating effect of α-MSH on the central acyl ghrelin-induced food intake, gastrointestinal motility, and colonic secretion in rats.Methods and procedures: We examined the effects of α-MSH and acyl ghrelin on food intake, gastric emptying, small intestinal transit, colonic motility, and secretion in conscious rats with a chronic implant of ICV catheters.Results: ICV injection of O-n-octanoylated ghrelin (0.1 nmol/rat) significantly increased the cumulative food intake up to 8 h (P<0.01), enhanced non-nutrient semi-liquid gastric emptying (P<0.001), increased the geometric center and running percentage of small intestinal transit (P<0.001), accelerated colonic transit time (P<0.05), and increased fecal pellet output (P<0.01) and total fecal weight (P<0.01). Pretreatment with ICV injection of α-MSH (1.0 and 2.0 nmol/rat) attenuated the acyl ghrelin-induced hyperphagic effect, fecal pellet output, and total fecal weight, while higher dose of α-MSH (2.0 nmol/rat) attenuated the increase in the geometric center of small intestinal transit (P<0.01). However, neither dose of α-MSH altered acyl ghrelin-stimulated gastroprokinetic effect, increase in the running percentage of small intestinal transit, nor accelerated colonic transit time.Conclusion: α-MSH is involved in central acyl ghrelin-elicited feeding, small intestinal transit, fecal pellet output, and fecal weight. α-MSH does not affect central acyl ghrelin-induced acceleration of gastric emptying and colonic transit time in rats. Keywords: acyl ghrelin, colon transit time, fecal pellet output, food intake, gastric emptying, intracerebroventricular, small intestinal transit, α-melanocyte stimulating hormone